Hubungan Paritas Terhadap Sikap Ibu Hamil dalam Mendeteksi Dini Komplikasi Kehamilan - Nurlina Nurlina; Nurbiah Eka Susanty; Erni Erni; Nurdiana Eka Nurdiana (Voice of Midwifery, 2023)
Pregnancy complications are obstetric emergencies that can cause death to the mother and baby. The existence of complications in pregnancy will have an impact on the health of the fetus and the risk for complications at birth, neonatal complications, impaired growth and development of toddlers. Parity is one of the determinants of the welfare of the mother and fetus during pregnancy and childbirth. This study aims to determine the relationship between parity and attitudes of pregnant women in early detection of pregnancy complications. This research is a cross sectional study, which was carried out from 01 to 30 November 2022 at the Kassi-Kassi Health Center in Makassar City. The sampling method was purposive sampling with a total of 30 respondents. Data processing used SPSS and data analysis was performed using the Spearman correlation test. Based on the results of the correlation test with Spearman, a correlation coefficient of 0.558 (p > 0.05) was obtained so that it can be concluded that parity has no significant relationship to maternal attitudes in early detection of pregnancy complications. There is no parity relationship with the mother's attitude in early detection of pregnancy complications. It is suggested that further researchers can examine other variables.